2003
DOI: 10.1063/1.1611270
|View full text |Cite
|
Sign up to set email alerts
|

Electron dynamics in InNxSb1−x

Abstract: Electron transport properties in InN x Sb 1Ϫx are investigated for a range of alloy compositions. The band structure of InN x Sb 1Ϫx is modeled using a modified k"p Hamiltonian. This enables the semiconductor statistics for a given x value to be calculated from the dispersion relation of the E Ϫ subband. These calculations reveal that for alloy compositions in the range 0.001рxр0.02 there is only a small variation of the carrier concentration at a given plasma frequency. A similar trend is observed for the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 9 publications
0
16
0
5
Order By: Relevance
“…It was experimentally indicated that [14][15][16][17], this atmospheric transition can access the range of 8-15 m when a small fraction of antimony is replaced by nitrogen in InSb. Time resolved optical measurements [15] have been used to observe an absorption edge of 15 m at 290 K in an alloy with a nominal composition of InN 0.006 As 0.994 .…”
Section: Inn X Sb 1−xmentioning
confidence: 98%
See 3 more Smart Citations
“…It was experimentally indicated that [14][15][16][17], this atmospheric transition can access the range of 8-15 m when a small fraction of antimony is replaced by nitrogen in InSb. Time resolved optical measurements [15] have been used to observe an absorption edge of 15 m at 290 K in an alloy with a nominal composition of InN 0.006 As 0.994 .…”
Section: Inn X Sb 1−xmentioning
confidence: 98%
“…To the knowledge of authors, there are a few works [9,10,[14][15][16][17]19,27] in which the electronic band structures of these ternary alloys have been studied theoretically. In most of these theoretical works, the ternary alloys were defined by only specific concentrations of N and As [9,[14][15][16][17]27]. In the present work, the electronic band structures of InN x As 1−x , InN x Sb 1−x and InAs x Sb 1−x alloys are calculated by empirical tight binding (ETB) method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an increased x value does not necessarily increase the effective mass at the Fermi level. 16 Nitrogen in the dilute InN x Sb 1Ϫx alloys grown using a mixed nitrogen and hydrogen plasma has been found to be bonded to both In and Sb and is also located in N-H complexes. Annealing for 8 h at 300°C partially removes hydrogen from N-H complexes and increases the amount of N bonded to In.…”
mentioning
confidence: 99%